Pengungkapan Emosi Dalam Pemasangan Display Picture BBM Berupa Wordpics Studi Deskriptif Kuantitatif Pengungkapan Emosi Dalam Pemasangan Display Picture Blackberry Messenger Berupa Wordpics Pada Siswa Sekolah Menengah Al Firdaus Sukoharjo) - Alfarizi, Muhammad Diauddin, Drs. Joko Sutarso, S.E, M.Si, Agus Triyono, M.Si (2016)
Muhammad Diauddin Alfarizi, L100110011, Disclosure Emotions In the Setup Display Picture BBM Form Wordpics (Descriptive Study Quantitative Disclosures Emotions In the Setup Display Picture Blackberry Messenger Form Wordpics At School Students Al Firdaus Sukoharjo), Thesis, Communication Studies, Faculty of Communication and Information, Universitas Muhammadiyah Surakarta, 2016. Blackberry Messenger (BBM) is an instant messaging application that is most widely used in Indonesia. Due to the activity of use and contact lists that are more personal than other applications, then the function Display Picture (DP) on fuel was also different, not only as a pointer identity, but sometimes as a medium of expressing emotions. See that emotion in social media has become a major problem in some studies, it is necessary to study the DP BBM to analyze the present invention. The purpose of this study was to describe the installation of expressing emotions in the form of wordpics BBM Display Picture by boys and girls SM Al Firdaus Sukoharjo. This research is quantitative research with descriptive approach. The population in this study were students SM Al Firdaus totaling 288 students, with a sample number of 170 students, and the sampling method used was stratified random sampling. The technique of collecting data using questionnaires. Data analysis techniques in this study using descriptive analysis. And the results of this research are: 1) On average, expressing emotions on mounting Display Picture BBM by female students is greater than male students, with an average score of items of 2.5566 on female students, while the average item scores -rata boys just 2.3798; 2) Based on the calculation of the items in the form of positive and negative emotions, showed that both boys and girls is higher in expressing positive emotions rather than emotions through DP BBM form Wordpics. Then if viewed by gender, then the average score of female students is higher than the average score of male students in both the positive and negative emotions; 3) The total score is the average of expressing emotions in the installation of the fuel in the form Wordpics DP on female students was higher than male students, which amounted to 79.2558 while male students only amounted to 73, 7738; 4) There are significant differences in the expression of emotions in the installation of DP BBM between male students and female students Firdaus SM AL Sukoharjo because sig 2 which is 0.003 <0.05.